Mediastinal Parathyroid Adenoma and Brown Tumors - P. Bernal; G. Ucros; A. Mejia (World Journal of Nuclear Medicine)
In this report, we describe a rare case of brown tumor and mediastinal parathyroid adenoma. This report emphasizes the value of radionuclide scintigraphy in the setting of persistent disease following parathyroid surgery.